نحو تفسير بلاغي جديد للنص القرآني؛ بعض ألفاظ سورة النساء أنموذجا - Elsayed Mohamed Salem Alawadi (IAIN Syekh Nurjati Cirebon, 2020)
كثر الكلام حول التجديد، والتخلي عن أدوات التفسير القديمة، والبحث عن غيرها لتقديم تفسير يتوافق مع جلالة النص ومواكبة العصر، وإن كانت كتب التفسير القديمة قد وفّت بحاجة الأزمنة التي صنعت فيها تلك الكتب، فهو لا تفي بحاجة هذا الزمان؛ إذ هي داعية إلى قول أجمع، وبيان أوسع، وبرهان أنصع في أسلوب أجذب للقلب، وأخلب للُّب، وأصغى للأسماع، وأدنى للإقناع، يتناسب مع عقول وأفهام هذا الزمان، وأدعى للإقبال بطريق أسهل، وعرض أيسر. ومن هنا جاء هذا البحث حلقة من حلقات الجهود المبذولة عبر التاريخ لبيان وتفسير إعجاز القرآن الكريم لِتُثْبِتَ سر تفرد بعض ألفاظ القرآن الكريم، وبيان جمالياتها وإظهار بلاغتها، وروعة سبكها، واتساقها مع ما وردت فيه سياقات متعددة من جميع زواياه. وسيستعين البحث بالمنهج التكاملي الذي يمزج بين المنهج التاريخي الذي يتتبع الظاهرة في أصل نشأتها، وأول من أطلقها واستعملها مروراً بها عبر الأزمنة إلى ما استقرت عليه الآن ، والمنهج التحليلي اللغوي والذي يفيد في تحليل الكلمات لغوياً لإدراك المعنى، ثم المنهج الوصفي الذي يرصد خصائص الظاهرة وملامحها،ثم بيان هذا التفرد، وآثاره البلاغية، وقيمته الجمالية. وسره البياني الذي يعتبر عملاً فنياً خالصاً ينطوي تحت المنهج الفني. وعليه جاءت الدراسة في مقدمة وتمهيد حول التجديد في علم التفسير، والمبحث الأول في معنى التجديد والتفسير، والثاني في تجديد التفسير، والثالث نموذج لتفسير بلاغي جديد، ثم خاتمة مشفوعة بمصادر البحث ومراجعه. ولعلي بهذا أضيف التفاتة جديدة للدراسات القرآنية، وفاءً للقرآن ، وإثراءً للغته . There is much talk about renewal, abandoning the old tools of interpretation, and looking for others to provide an interpretation that is compatible with the Majesty of the text and keeping up with the times, although the old books of interpretation have fulfilled the times when they were made, they do not meet the need of this time; The first is to say a lot, a broader statement, a proof that is in a way that attracts the heart, a liar, a sore, a listen, a less persuasion, fits in with the minds and thoughts of this time, and an easier way to present the reception. This research came from a series of efforts made throughout history to explain and interpret the Qur'an's miracles to prove the uniqueness of some of the Holy Qur'an's words, to illustrate its esthetics and to show its language, the awe of its scope and its consistency with the various contexts in which it was mentioned. The research will use the complementary approach, which combines the historical approach that follows the phenomenon in its origin, and the first to launch and use it through times to its stability The language analysis approach, which is useful in parsing words to understand meaning, then the descriptive approach that monitors the characteristics and features of the phenomenon, then the uniqueness, its rhetorical effects, and its esthetic value. His graph, which is a work of art, is involved under the technical curriculum. The study thus came in the introduction to and the beginning of the innovation in the science of interpretation, the first in the meaning of renewal and interpretation, the second in the renewal of interpretation, the third in the model of interpretation of a new communication, and the final, with the sources and references of research. This is not to say that the new chapter of Qur'anic studies, in fulfillment of the Qur'an, and enrichment of its language, has been added.